Are Turkey's tourism markets converging? Evidence from the two-step LM and three-step RALS-LM unit root tests - Ozcan, Burcu; Erdogan, Seyfettin (Routledge Journals, Taylor & Francis Ltd, 2017)
In this study, we aim to analyse whether Turkey's 14 major tourist source markets are converging by using monthly data over the period January 1996 to December 2012. To this aim, we use the recently developed two-step Lagrange multiplier (LM) and three-step residual augmented least squares-Lagrange multiplier (RALS-LM) unit root tests that allow for two structural breaks in data. The results indicate that 10 out of 14 markets are converging, meaning that tourism policies and strategies directed at these markets are successful. Furthermore, the break points correspond to the important political, social, natural and economic events such as crisis, earthquake, disease and terrorist attack.
Keywords: tourism markets; tourism policy; convergence; structural breaks; unit root test